Expectations about pain management after discharge from total hip and knee replacement surgery: a qualitative study with patients and prescribers - Liang, Ian; Youssef, Peter; Haynes, Abby; Lin, Chung-Wei Christine; Harris, Ian; Horsley, Mark; Jones, Caitlin M. P. (Frontiers in Pain Research, 2025)
ObjectiveThis study aimed to explore the perspectives of both patients and prescribers regarding analgesia after discharge following total hip or knee replacement surgeries, focusing on opioid use and the factors influencing patient and prescriber decision making.MethodsSemi-structured interviews were conducted with 20 prescribers and 13 patients. 6 patients were interviewed before and after surgery. Thematic analysis of the data was conducted by three researchers.ResultsFor prescribers, three key themes were identified: (1) A patchwork of prescribing practices with diverse influences on health professional’s decisions, including the ‘norm’ of each site; (2) What counts as evidence for practice? in which prescribers relied on clinical experience, more than guidelines; And (3) Risk-benefit trade-offs that prescribers make when challenged to treat pain while minimising side effects. Analysis of patients’ data also identified three key themes: (1) (Unfulfilled) expectations of careful pain management such as evidence-based decisions and close monitoring to avoid harm; (2) Risk-benefit trade-offs: fear of pain vs. fear of side effects including anxiety about both expected pain and expected side effects, and (3) Variation in self-management of opioid use due to varying interpretation of vague instructions. The views and expectations of prescribers and patients differ and sometimes conflict with each other.ConclusionThis research highlights the need for improved guidance for both prescribers and patients, and clearer communication to optimise the management of pain after discharge.